1999
DOI: 10.1023/a:1003690102610
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Three distinct types of Tc1-family transposable elements have been identified in the malaria vector, Anopheles gambiae. These three elements, named Tsessebe, Topi and Tiang, have the potential to encode transposases that retain most of the conserved amino acids that are characteristic of this transposon family. However, all three are diverged from each other by more than 50% at the nucleotide level. Full-length genomic clones of two types, Topi and Tsessebe, have been isolated and fully sequenced. The third, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…DD34E/ Tc1 is a classical family of Tc1/mariner transposons, first found in C. elegans in the 1980s [ 17 ], and displays extensive distribution in nature [ 28 ]. Diverse DD34E/ Tc1 transposons were discovered in multiple lineages of animals, including Topi and Quetzal in mosquitoes [ 48 , 60 ], Impala in fungi [ 30 ], Minos , S elements and Bari-3 in fruit flies [ 49 , 50 , 53 ], Frog Prince in frogs [ 32 ], and Passport in fish [ 26 ]. The DD34E/ Tc1 group was then divided into at least five distinct clusters based on the DD34E/ Tc1 elements identified from six teleost species in our earlier study, combined with previously reported elements of this family from other laboratories [ 58 ]; however, the intra-family diversity is still ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…DD34E/ Tc1 is a classical family of Tc1/mariner transposons, first found in C. elegans in the 1980s [ 17 ], and displays extensive distribution in nature [ 28 ]. Diverse DD34E/ Tc1 transposons were discovered in multiple lineages of animals, including Topi and Quetzal in mosquitoes [ 48 , 60 ], Impala in fungi [ 30 ], Minos , S elements and Bari-3 in fruit flies [ 49 , 50 , 53 ], Frog Prince in frogs [ 32 ], and Passport in fish [ 26 ]. The DD34E/ Tc1 group was then divided into at least five distinct clusters based on the DD34E/ Tc1 elements identified from six teleost species in our earlier study, combined with previously reported elements of this family from other laboratories [ 58 ]; however, the intra-family diversity is still ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…A few samples in tier I are slightly more AT-rich than others. (21). § MER30 and MER44A are MITEs found in man (10).…”
Section: Diverse Families Of Mites In a Gambiaementioning
confidence: 99%
“…The similarities to different DNA transposons at the insertion target and the TIRs support the hypothesis that MITEs may have been borrowing the transposition machinery from autonomous DNA transposons. As discussed above, Tsessebe I, a Tc1-pogo type DNA transposon in A. gambiae (21), share similar TIRs with some of the A. gambiae MITEs. However, it is not clear whether Tsessebe I had been involved in mobilizing these MITEs because the similarities between their TIRs are limited.…”
Section: Diverse Families Of Mites In a Gambiaementioning
confidence: 86%
“…As shown in Table 2, more than half of the TA-specific MITEs in A. gambiae share similar terminal repeats with a TA-specific MITE in man and a Mimo element in a Culex mosquito (10,16). These MITEs also share similar TIRs with a few Tc1-pogo DNA transposons including Tsessebe I of A. gambiae (21). The phrase ''DNA transposon'' here refers to a DNA element that has the coding capacity for its transposase, which may or may not be still active.…”
Section: Diverse Families Of Mites In a Gambiaementioning
confidence: 94%